Authentic leadership among academics and administrative staff in IIUM - Hashim, Che Noraini; Opatokun, Khadijah (2011)
Leadership is critical to the success of all organization, higher institutions are no exception. Contemporary leadership theories and practices describe authentic leadership (AL) in relation to self-awareness, relational transparency, internalized moral perspective, and balance processing of information. The study examines the convergent and discriminant validity of the four dimensions of authentic leadership in the academic administration. A total of 438 academic and administrative staff at the International Islamic University Malaysia were asked to rate their authentic leadership behaviours. Findings from principal component analysis (PCA) revealed three dimensions (internalized moral perspective, self-awareness, and relational transparency) of authentic leadership instead of four dimensions proposed by Walumba, et al. (2008). The result also provides evidence that supports discriminant validity and none on convergent validity. Additionally, confirmatory factor analysis (CFA) was employed to test the dimensions. The result from the confirmatory analysis support the dimensions obtained from PCA. Consequently there are no differences in the rating of both the academic and administrative staff, despite the gap in the contextual variables (e.g. gender, academic qualification, number of years employed and age).